Isolation, characterization, and genomic analysis of three novel Herelleviridae family lytic bacteriophages against uropathogenic isolates of Staphylococcus saprophyticus - Hesamaddin Shirzad-Aski; Mahsa Yazdi; Alireza Mohebbi; Maryam Rafiee; Abbas Soleimani-Delfan; Alijan Tabarraei; Ezzat Allah Ghaemi (Virology Journal)
Abstract Background Staphylococcus saprophyticus (S. saprophyticus) is the second most prevalent etiological agent of urinary tract infections (UTIs) in young women. However, there is a paucity of data regarding its bacteriophage (phage). Therefore, this study was conducted to isolate and identify new lytic phages from municipal wastewater with the objective of increasing knowledge about phages and their genomes. Methods A total of 11 clinical isolates of S. saprophyticus and 30 wastewater samples were used to isolate three lytic phages (vB_SsapH-Golestan-100, vB_SsapH-Golestan101-M, and vB_SsapH-Golestan-105-M). The morphology, behavioral characteristics, and complete DNA genomes of these phages were analyzed. Results The microscopic images of the phages revealed that the sizes of their heads and tail lengths fell within the ranges of 90–111 nm and 234–266 nm, respectively. All phages exhibited high adsorption rates (99.5% in 15 min) and burst sizes (150–210 PFU per infected cell), with a potential for a narrow host range. Genomic analysis of Staphylococcus phages indicated a size of 136,433 base pairs (bp) with a guanine-cytosine (GC) content of 33.7% and 192 open reading frames (ORFs) for vB_SsapH-Golestan-100, 144,081 bp with a GC content of 29.6% and 205 ORFs for vB_SsapH-Golestan101-M, and 142,199 bp with a GC content of 30.6% and 203 ORFs for vB_SsapH-Golestan-105-M. A bioinformatics analysis indicated that all three phages belong to the Twortvirinae subfamily of Herelleviridae. Among the three phages, vB_SsapH-Golestan-100 exhibited the least similarity to previously known phages, with less than 21% similarity with its closest counterparts in genomic databases. Conclusions This study identified new phages that have the ability to destroy a broad range of S. saprophyticus isolates and may potentially be classified as a new genus and species within the Herelleviridae family in future studies.